Insurance in the light of religious teaching and ethics: a case study of India - Salman, Syed Ahmed; Htay, Sheila Nu Nu (IDOSI Publications, 2014)
Ethics is an essential foundation of any religious teaching. One fundamental ethic advocated by all religions is justice from which extends treating others within the parameters of what is fair and just. This is an important premise for understanding the development of insurance. Historically, in India, the insurance industry was nationalized due to the unethical practices of insurance companies. Although this industry is currently opened to the private companies, the majority of market share remains with public owned insurance companies such as Life Insurance Corporation of India (LIC) and the General Insurance Corporation of Insurance (GIC). In addition, there is only one reinsurance company in India and it is government owned. Thus, through public insurance companies, the Indian government has a controlling say in the insurance industry in India. Here, one may question as to why, despite the many years of government influence in the insurance market, the government is still reluctant to return the insurance sector to private control or market forces. In an attempt to answer this postulate, this paper argues that a number the presence of unethical practices remains significant therefore requiring the introduction of ethics based insurance in India. This research is a conceptual paper based on qualitative research. Ethical values from six religions are discussed, namely Christianity, Judaism, Islam, Sikhism, Hinduism and Buddhism. It is expected that the findings of this research will be of interest to insurance companies, investors, policy holders, consultants, regulators and the general public general